2016
DOI: 10.4314/tjpr.v14i12.25
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Pharmacological Properties of the Genus Melodinus – A Review

Abstract: Melodinus is an important genus comprising of approximately 53 species of medicinal plants (Apocynaceae). Some species have been used in Chinese folk medicine for the treatment of meningitis in children, rheumatic heart diseases, and diuresis, as well as a decongestive against migraine and sinusitis. This paper is a review of the literature up to May 2015 and describes 263 compounds from 69 articles, and includes chemical constituents isolated from Melodinus, mainly indole alkaloids, quinoline alkaloids, dimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 39 publications
(100 reference statements)
0
15
0
Order By: Relevance
“…research showed that about 66 alkaloids of different structures have been isolated from M. henryi so far [8,[12][13][14]19]. In this study, 15 monoterpenoid indole alkaloids were isolated and identified.…”
Section: Aggregationsmentioning
confidence: 82%
See 4 more Smart Citations
“…research showed that about 66 alkaloids of different structures have been isolated from M. henryi so far [8,[12][13][14]19]. In this study, 15 monoterpenoid indole alkaloids were isolated and identified.…”
Section: Aggregationsmentioning
confidence: 82%
“…Furthermore, there is an urgent need for phytochemical investigation on bioactive ingredients of this plant to understand the chemical components of MHTA. Phytochemical research showed that about 66 alkaloids of different structures have been isolated from M. henryi so far [ 8 , 12 14 , 19 ]. In this study, 15 monoterpenoid indole alkaloids were isolated and identified.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations